The test of war inside Britain 1939-45 - Mackay, Robert 1940- (UCL Press, 1999)
While it lasted, the Second World War dominated the life of the nations that were involved and most of those that were not. Since Britain was in at both the start and the finish her people experienced the impact of total ar in full measure. The experience was a test of the most comprehensive kind: of the institutions, of the resources, and the very cohesion of the nation. The Test of War by Robert Mackay examines how the nation responded to this test. For a generation after the ending of the war this response was represented as largely unproblematical: faced with mortal threat to their survival the people rallied around their leaders, sank their differences and bore the burdens and sacrifices that were necessary to victory. More recently, demurring voices have challeged this cosy picture by emphasizing negative features of the war as official muddle, low industrial productivity and strikes, the black market, looting and the persistence of hostile class relations. Robert Mackay re-examines these debates, arguing that, for all its imperfections, British society under threat remained vital, cohesive and optimistically creative about its future.